Carbon nanomaterials in tribology. (August 2017) - Zhai, Wenzheng; Srikanth, Narasimalu; Kong, Ling Bing; Zhou, Kun
Abstract: Over the past two decades, carbon nanomaterials have attracted great interest for their confirmed friction and wear performances as well as important tribological applications. This article gives a comprehensive review of the recent developments of four typical carbon nanomaterials including fullerenes, carbon nanotubes (CNTs), graphene and nanodiamonds in tribology. Firstly, the applications of the four types of carbon nanomaterials in coatings for anti-wear enhancement and friction reduction are discussed. Secondly, the improvement of tribological behaviors for bulk materials by using CNTs, graphene and nanodiamonds as additives is reviewed. Thirdly, the discussion is conducted on the mechanisms of the fullerenes, CNTs, graphene and nanodiamonds acting as additives in lubricants to achieve friction and wear reduction. Fourthly, the progress on superlubricity using CNTs and graphene is highlighted. Finally, this review concludes with an outlook of the future studies on carbon nanomaterials in tribology, their key challenges for commercial applications, and possible solutions. Graphical abstract: